Analysis of Acromatic Acids in River Water by Non-Aqueous Capillary Electrophoresis with Electrokinetic Supercharging - Ning, Z.; Sui, L.; Zhong, H.; Li, Y.; Li, R. (Asian Journal of Chemistry, 2011)
Electrokinetic supercharging (EKS), a new and powerful on-line preconcentration method for capillary electrophoresis, was utilized in non-aqueous capillary electrophoresis (NACE) to enhance the sensitivity of acromatic acids. The buffer acidity and concentration, leader and terminator length and electrokinetic injection time were optimized, with the optimum conditions being: a background electrolyte of 30 mmolL-1 tris-acetic acid (pH 7.9), hydrodynamic injecting of 100 mmol L-1 ammonium chloride (22 s, 0.5 psi) as leader, electrokinetic injection of the sample (200 s, -10 kV), hydrodynamic injecting of 10 mmol L-1 2-(cyclohexylamino)ethanesulphonic acid (32 s, 0.5 psi) as terminator, before separation (-25 kV). Under these conditions the sensitivity was enhanced between 3868-6480 times when compared to a normal hydrodynamic injection. Detection limits for the five aromatic acids were in the range of 0.08-0.30 ng mL-1. The developed method was further verified by application to river water real sample analysis and with good results.